Understanding Financial Behavior Among Students: A Literature Review on the Risks of Falling into Online Loan Debt - Geriadi, Made Ayu Desy; Dwijayanthi, A.A.Istri Agung Ovy (Global Researcher Network, 2024)
The rapid expansion of online loan services has led to increased financial risks for students, particularly in Indonesia, where access to digital financial services has become ubiquitous. This literature review explores the financial behavior of students, focusing on their engagement with online loan platforms and the associated risks of falling into debt. Financial literacy, peer influence, family background, and psychological factors such as impulsivity and risk-taking behavior are identified as key determinants of students' borrowing decisions. While financial literacy plays a crucial role in helping students make informed decisions, low financial literacy levels increase their susceptibility to predatory lending practices. Additionally, peer influence, social norms, and the allure of instant gratification contribute to the normalization of online loans among students. The review highlights the importance of digital financial literacy programs and interventions aimed at improving students' ability to navigate online financial services responsibly. Finally, the study identifies several gaps in the literature, including the need for longitudinal studies, an exploration of the psychological drivers of online loan usage, and research into the impact of online loan marketing strategies. This review provides valuable insights for policymakers, educators, and financial institutions seeking to mitigate the risks of online loan debt among students.